ANALISA DAN PERANCANGAN SISTEM INFORMASI DISTRIBUSI LIQUID VAPE PADA SOLUTION VAPE STATIONSTORE - Raditya Imam Maulana, - (2018)
This research is a case study in Solution Vape Station Store. The purpose of this final project is to create a liquid vape distribution information system on a website-based solution vape station in order to manage web-based liquid vape distribution data that can be accessed by solution vape station store distributor owners with vape retailers. It aims to improve comfort and efficiency in distributing liquid vape. Data were analyzed using the PIECES method while the design applied the OOAD method or Object Oriented Analysis and Design with the Unified Modeling Languang tools. Expected results are expected to help solve the problems faced by the Solution Vape Station Store Distributor in order to facilitate the flow of goods from the distributor to retailers and help Solution Vape Station Store Distributors develop distribution systems to expand the range of product distribution so as to provide convenience and speed to retailers receive goods, return of goods and the increasing number of retailers that can be seized or invited to cooperate so that sales can increase